Pembelajaran Sejarah Berbasis Higher Order Thinking Skill (HOTS) sebagai Implementasi SDG 4 (Quality Education) - Chairunnisa Mardiah Ramadhani; Yuma Laberty Ibadi; Cyndi Felisya; Sani Safitri; Rani Oktapiani (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
History learning plays a strategic role in developing students’ critical, analytical, and reflective thinking skills. However, instructional practices that still emphasize memorization of facts often fail to foster higher-order thinking abilities. This article aims to examine the implementation of Higher Order Thinking Skills (HOTS)-based history learning as an effort to support the achievement of Sustainable Development Goal (SDG) 4, namely quality education. The HOTS approach in history learning emphasizes students’ abilities to analyze, evaluate, and create through activities such as interpreting historical sources, solving contextual problems, and engaging in critical discussions of past events. The method used in this study is a literature review by analyzing various sources related to HOTS-based learning strategies and their implementation in history education. The findings indicate that the application of HOTS enhances student engagement, deepens conceptual understanding, and fosters historical awareness relevant to contemporary life. In addition, HOTS-based learning encourages students to develop reflective thinking and make better-informed decisions. The implementation of HOTS in history learning aligns with the principles of SDG 4, which emphasize inclusive, equitable, and quality education. Therefore, integrating HOTS into history instruction not only improves the quality of the learning process but also contributes to the development of a generation that is critical, creative, and adaptive in facing global challenges.